ChemInform Abstract: Coumarins: Facile and Expeditious Synthesis via Keggin‐Type Heteropolycompounds under Solvent‐Free Condition. Issue 7 (18th February 2014) - Rafiee, Ezzat; Fakhri, Akram; Joshaghani, Mohammad
Abstract Rapid procedures for the synthesis of structurally diverse coumarin derivatives via Pechmann reactions of acetoacetates with mono‐ or polyphenols are described using supported heteropoly‐compounds as catalyst.